2022
DOI: 10.1101/2022.02.17.480955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ architecture of human kinetochore-microtubule interface visualized by cryo-electron tomography

Abstract: Chromosome segregation during mitosis relies on a carefully coordinated interplay between the centromere, kinetochore, and spindle microtubules. Despite its importance, the architecture of this interface remains elusive. Here we combined in situ cryo-electron tomography and cryo-light microscopy to visualize the native architecture of the kinetochore-microtubule interface in human U2OS cells at different stages of mitosis. Our data reveal that upon microtubule binding, the centromere forms a pocket-like struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Ribosomes are located near the surface of the compacted chromosomes (Figure 4A), consistent with previous analysis of both HeLa cell cryosections (Eltsov et al ., 2008), U2OS cryolamellae (Zhao & Jensen, 2022), our cryosections (Figure S2), and isolated metaphase chromosomes (Nishino et al , 2012). Spindle microtubules that are inserted into metaphase chromosomes were previously observed in U2OS cells (Kamasaki et al , 2013) and are also seen in the RPE-1 chromosomes (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribosomes are located near the surface of the compacted chromosomes (Figure 4A), consistent with previous analysis of both HeLa cell cryosections (Eltsov et al ., 2008), U2OS cryolamellae (Zhao & Jensen, 2022), our cryosections (Figure S2), and isolated metaphase chromosomes (Nishino et al , 2012). Spindle microtubules that are inserted into metaphase chromosomes were previously observed in U2OS cells (Kamasaki et al , 2013) and are also seen in the RPE-1 chromosomes (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In our cryotomograms of metaphase cells, the canonical nucleosomes are uniformly distributed within the compacted chromosomes (with the exception of pockets; see below), i.e., we did not observe separate domain-like features within the metaphase chromatin. Human metaphase chromatin has also been studied in situ in 3-D by Chrom-EMT (Ou et al ., 2017) and cryo-ET of cryo-FIB-milled cells (Zhao & Jensen, 2022). Neither of these EM-based studies reported any nanodomain-like features in mitotic chromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetochores have also been revealed to influence and organise the surrounding chromatid, establishing them as much more than machines that couple chromosomes to microtubules. Indeed, in situ cryo-electron tomography now shows how the human kinetochore is sitting within a centromeric chromatin pocket with expected filamentlike linkages to microtubules visible (274).…”
Section: Discussionmentioning
confidence: 99%
“…These k-units have been isolated from cells and can be visualised by electron microscopy (( 84 Similar counting experiments in human cells estimated ∼244 NDC80C per kinetochore (233). Recent electron tomography now indicates there may be only ~10 microtubules per human kinetochore (122,181,274). This gives ~24 NDC80C per MT in humans.…”
Section: Working Model For the Kinetochore-centromere Super-clustermentioning
confidence: 99%